Hubungan Motivasi dan Disiplin Belajar terhadap Hasil Belajar pada Mata Pelajaran Bubut Kelas XI Teknik Permesinan di SMK Dhuafa Padang - Ilham Ilham; Rizky Ema Wulansari; Purwantono Purwantono; Eko Indrawan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
This study describes the relationship between motivation and student learning discipline towards learning outcomes in the lathe subject. The purpose of this study was to determine the relationship between motivation and learning discipline towards learning outcomes in the lathe subject of class XI students of Mechanical Engineering at SMK Dhuafa Padang. Hypothesis testing in this study used a simple correlation test and multiple product moment correlation to determine the relationship between motivation and learning discipline variables with learning outcomes in the Lathe Subject. This study was conducted at SMK Dhuafa Padang, and the subjects were class XI students of Mechanical Engineering with a sample size of 21 students. The results of the research data analysis showed that there was a positive and significant relationship between learning motivation and learning discipline together towards learning outcomes in the Lathe Subject of Class XI Mechanical Engineering at SMK Dhuafa Padang. This is evidenced by the research data that rhitung> rtable, which is 0.535> 0.413 at a significance level of 5%. By recognizing the important relationship between learning motivation and academic achievement, educational institutions and educators can implement more efficient strategies to enhance students' enthusiasm for learning in order to achieve optimal learning achievement in mechanical engineering lessons.